ANALYSIS ON THE DIFFICULTIES OF SMAN 1 SUNGAI LALA STUDENTS IN WRITING HORTATORY EXPOSITION TEXT - Niam, Ikfina Bi; Aruan, Rumiri; Prawati, Atni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to find out the difficulties of the second-year studentsof SMAN 1 Sungai Lala in writing hortatory exposition texts. This study was descriptivequantitative research. The writer used a systematic sampling technique to decide thesample. From 133 students of the total population, the writer selected 50 students’ asthe sample. A written test and questionnaire were applied to collect the data. Thefinding shows that the student’s ability in writing hortatory exposition text is atmediocre levels. The aspect of difficulties that faced by the students are the contentaspect with the mean score 17.07, language use 15.93, mechanics 3.24 andorganization 13.85 that considered as fair to poor level. Furthermore, the otherstudents difficulty was found from the questionnaire where the higher indicator iscognitive difficulties that considered as good level with the percentage 70.32%(3.51).The result showed that the second grade students of SMAN 1 Sungai Lala havedifficulties in writing hortatory exposition text.Key Words: Analysis, Difficulties, Writing Skill, Hortatory Exposition Text